Assessment of the Environmental Impact of Drug Products Using Life Cycle Assessment: A Case Study in a Pharmaceutical Company, Semarang - Sri Hartini; Diana Puspita Sari; Dian Tri Kusuma Ningrum (Universitas Diponegoro, 2023)
The pharmaceutical production process produces 55% greater emission intensity than the automotive industry. Along with increasing attention to the environmental impact of pharmaceutical drugs, pharmaceutical companies need to know the impact resulting from their production processes. This study analyzes the environmental impact of the anti-hangover drug production process using a Life Cycle Assessment. The analysis was carried out on 1 batch which produced 1,000,000 drugs. The scope of the gate to gate study from the initial process to the end of production. The research objective was to determine the potential impact resulting from the drug production process on the environment. The indicator measured is eco-cost, which is the cost of environmental impact calculated using the SimaPro software. This study found that the eco cost was IDR 3,931,237.65 with the largest environmental costs in the packaging process and the largest impact indicator on climate change. The biggest source of impact comes from the consumption of electrical energy. This study recommends the use of solar panels. For the energy conversion process, 80 KWp is needed with 288 solar panels and a land requirement of 0.564 Ha. This recommendation is estimated to reduce 22% percent of environmental costs.